ANALISIS WACANA PENULISAN BERITA ANTARA WARTAWAN WANITA DAN PRIA TENTANG PELECEHAN SEKSUAL DI DETIK.COM - Yanti, Basrah (Social Humanity: Jurnal Ilmu Sosial dan Humaniora, 2019)
The purpose of this study was to find out how to write news stories between female and male journalists about sexual harassment in the online media Detikcom. The research method used in this research is descriptive qualitative, using discourse analysis methods Roger Fowler, Robert Hodge, Gunther Kress, and Tony Trew. This analysis uses elements of vocabulary and grammar. Vocabulary is divided into four, namely classification, limiting views and marginalization. Then the grammatical elements are divided into two, namely passivation and nominalization. The object of this research is sexual harassment news on the Detiknews website on the Detikcom portal as many as 6 news stories with 3 topics, divided into 3 news writing by women and 3 news writing by men, from February to August 2014. The results of the research are seen from the elements of vocabulary and grammar. , according to Roger Fowler, Robert Hodge, Gunther Kress, and Toni Trew. The significant difference in women's and men's news writing about sexual harassment in Detikcom's online media, is only in the element of limiting views where male writers are more likely to use the word euphemism than female news writers. and on the element of marginalization men tend to marginalize actors badly. while the other elements are different but not as significant as the elements of limiting views and marginalization, because the researcher only focuses on the subtle aspects and whether or not the language used by female and male news writers about sexual harassment in the online media Detikcom.